MARTIN-BRADLEY MODEL: DISCRIMINATE ACADEMIC PERFORMANCE BASED ON THE SELF-CONCEPT OF FRESHMEN - Tattao, Luis Arlantico (European Scientific Journal, ESJ, 2014)
The Martin-Bradley Discriminant Model (MDM) was used to discriminate the academic performance of freshmen engineering students based on their self-concept scores. The modified self-concept scale, with a total of 32 items of which 8, 10, and 14 descriptors about personal worth, accepting attitudes, peer relations respectively, was used to 800 freshmen of the Don Mariano Marcos Memorial State University – Mid-La Union Campus which has an enrolment of 5875 students. Personal worth, accepting attitudes, peer relations seemed to be good criteria that can discriminate between students with low academic performance from those with high academic performance. The model indicated that students exhibiting high scores in at least two self-concept factors performed high academically and students showing low scores in at least two self-concept factors performed low academically. Among the self-concept factors, accepting attitudes was found the best indicator of academic performance.